The Influence of Ecoprint Batik Iron Blanket Technique on Increasing Early Childhood Creativity - Sitti Nurhidayah Ilyas; Rika Kurnia R.; Fitriani Dzulfadhilah; Sri Rika Amriani H; Angri Lismayani (Universitas Muhammadiyah Enrekang, 2023)
Early creativity is important to stimulate because it contributes to various aspects of development, including cognitive skills, adaptability, self-expression, social skills, motor skills and children's imagination. The study in the research intends to review the effectiveness of the iron blanket technique in the application of ecoprinting using natural materials as media on the creativity of children aged 5-6 years. The posttest only nonequivalent control group design was used in this type of quantitative research with data collection techniques in the form of tests and observations. The sample amounted to 28 early childhood students. Descriptive statistical analysis and inferential analysis are the data analysis techniques chosen. The conclusion of this study based on the data shows that ecoprint with iron blanket technique can improve children's creativity, but the ecopounding or steam technique is more effective, this result is supported by the data Tℎ